Adapting During the Ever-Changing Pandemic Environment: A One-Year Examination of How Health Education Specialists Remain Adaptable. Issue 3 (4th May 2022) - Yazel, Lisa; Bishop, Charity; Britt, Hannah
ABSTRACT: Background: The COVID-19 pandemic has affected the public health profession as a whole, but there is little evidence of the effects on the health education specialist (HES) field. Early publications show that HES shifted and adapted to COVID-19 priorities, but there is no data to track this over time. Purpose: The purpose of this study was to examine HES' perspectives of their roles and responsibilities at one year post the start of the COVID-19 pandemic. Methods: A convenience sample of 15 HES took part in brief qualitative interviews during March 2021, one year post the pandemic start in the U.S. Results: Study results show that HES are adaptable to the changing needs of their roles and responsibilities, with four factors contributing to adaptability, namely shift in priority, productivity/work-life balance, importance of public health, and job security. Discussion: While respondents reported adaptability at one year, there is little evidence to explain this phenomenon, lending to further exploration of how HES work under a code of ethics, their willingness to work outside of their current work roles, and vocational theory. Translation to Health Education Practice: Many factors that will determine HES' adaptability, therefore, practitioners should be monitored and assessed over time. A AJHE Self-Study quiz is online for this article via the SHAPE America Online Institute (SAOI)http://portal.shapeamerica.org/trn-Webinars